A bulk effect liquid-solid generator with 3D electrodes for wave energy harvesting. (September 2021) - Gu, Haojie; Zhang, Nan; Zhou, Zhiyuan; Ye, Shimeng; Wang, Wenjie; Xu, Wanghuai; Zheng, Huanxi; Song, Yuxin; Jiao, Jiwei; Wang, Zuankai; Zhou, Xiaofeng
Abstract: Wave energy is one of the most promising renewable energy sources. The approaches for wave energy harvesting have been attracting more and more attentions all over the world. Although triboelectric nanogenerators (TENGs) based on liquid-solid interface have offered a new method for wave energy harvesting, some challenges still remain such as the relatively low energy power density and energy conversion efficiency. Here, we introduce a liquid-solid generator with electrode arrays that allows for improved wave energy harvesting compared to conventional TENG. The design of 3D electrodes above dielectric layer engenders a bulk effect that connect the electrode array, the polymer layer and bulk water into a closed-looped system. The arrayed generator can also be assembled easily and the instantaneous output power density can be enhanced from 2.7 W/m 2 to 11.7 W/m 2 with the 3D electrodes. We envision that this bulk effect generator based on liquid-solid interface will open new insight in blue energy harvesting in the future. Graphical Abstract: ga1 Highlights: ● A liquid-solid generator based on bulk effect for wave energy harvesting has been realized. ● Following the design of 3D electrodes, the bulk effect liquid-solid generator can output high current of 4 mA. ● Through the arrangement of arrayed generator, a high instantaneous power density of 11.7 W/m 2 is achieved.